U-Pb sensitive high-resolution ion microprobe ages from the Doushantuo Formation in south China: Constraints on late Neoproterozoic glaciations - Zhang, SH; Jiang, GQ; Zhang, JM; Song, B; Kennedy, MJ; Christie-Blick, N (Geology, 2005)
Two distinctive volcanic ash beds were found in the terminal Proterozoic Doushantuo Formation in south China. The lower ash bed, similar to 2.5 m above the cap carbonate at the base of the Doushantuo, yields a U-Pb zircon age of 621 :+/- 7 Ma, providing the closest upper limit for a correlative of the Marinoan glaciation. The upper ash bed, near the Doushantuo-Dengying boundary, yields a U-Pb zircon age of 555.2 +/- 6.1 Ma, providing for the first time a direct age determination for a prominent negative delta(13)C excursion above the Marinoan glacial level. This excursion, if interpreted to be of glacial origin, is much younger than the Gaskiers Formation (ca. 580 Ma) in Newfoundland, and perhaps the fifth or sixth such level in the Neoproterozoic. That interpretation, however, is not supported by the proliferation of organisms within strata encompassing the negative delta(13)C excursion in south China and globally, by the lack of a ca. 555 Ma glacial record, and by the absence of stratigraphic evidence for sea-level change. The data call for alternative paleoceanographic models for the origin of Neoproterozoic delta(13)C excursions not clearly related to glaciation.